مدارج النبوۃ کا اسلوب و خصوصیات : ایک تحقیقی مطالعہ (Al-Qamar, 2022)
The writer of “Madārij-al-Nubuwwah” Sheikh Abdul Haq Muhaddis Dehlvi is considered one of the renowned scholars and Muhaddisin of the sub-continent, who spent all his life in the promulgation and publication of Hadith and Seerat-ul-Nabi (S.A.W). His book “Madārij-al-Nubuwwah” is world renowned on Seerat-ul-Nabi and his great scholarly achievement, which was requirement for the conditions of this age. The basic/fundamental problem of this age was to develop misunderstanding about Madārij- Nubuwwah and Risalah (Prophethood), and a number of people/a lot of people were involved in this critical misconception/ mis-interpretation that only believe in Allah Almighty is complete faith, the Nubuwwah and Risalah (Prophethood) of Muhammad (PBUH) is not compulsory/obligatory part of faith/creed. Therefore, it was necessary to create a relation with the Rasool Akram (SAW) along with the study of Quran and Sunnat to develop the love and affection of Din Islam. No Indian Muslim has ever compiled such authentic, detailed and complete book on Seerat before it. This book is a source and model for the upcoming Seerat writers.
Keywords: Abdul Haq; Madārij-al-Nubuwwah; Characteristics; Methodology